2022
DOI: 10.3390/s22197136
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Scene Monitoring for Deaf-Blind People

Abstract: It is estimated that at least 15 million people worldwide live with severe deaf-blindness, with many more experiencing varying degrees of deaf-blindness. The existing options of assistance are mostly limited to walking canes, guide dogs and human care. We propose a wearable device which harnesses a multi-antenna mmWave radar transceiver and a haptic feedback array for real time detection of a person moving within a scene. We present our findings from a series of workshops with participants classed with multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…If we are to build a fairer, more inclusive society for the deafblind community, we need to remove the existing barriers and learn from them about their perception and needs. One way is to utilise new sensory modalities (e.g., with haptic technologies -see Kassem et al, 2022) and create environments that enrich diverse modes of experiences and communications. Deafblindness needs to be more central to our understanding of different perceptual experiences.…”
Section: Discussionmentioning
confidence: 99%
“…If we are to build a fairer, more inclusive society for the deafblind community, we need to remove the existing barriers and learn from them about their perception and needs. One way is to utilise new sensory modalities (e.g., with haptic technologies -see Kassem et al, 2022) and create environments that enrich diverse modes of experiences and communications. Deafblindness needs to be more central to our understanding of different perceptual experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct guidance systems installed on various guiding apparatuses are made up of various assistive guidance technologies. One innovative solution for the visually handicapped is the guide helmet [11], which uses cutting-edge sensor technology like LiDAR to identify obstacles and provide real-time spatial awareness. Users are provided with an intuitive grasp of their surroundings through the processing and transformation of the acquired data into haptic or audible warnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Beebe et al, (2020) in their review article focus on the use of scent-detection dogs in various fields, such as detecting drugs, explosives, and human diseases. Again, authors reported in their review article about the history, prevalence, and characteristics of guide dogs used by individuals with visual impairments (Kassem et al, 2022). In addition, Mueller et al, (2018) also, explore the positive impact of therapy dogs on the well-being of elderly individuals.…”
Section: Feil Et Al (2021)mentioning
confidence: 99%